2019
DOI: 10.1016/j.preteyeres.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

New concepts in the diagnosis and management of choroidal metastases

Abstract: The most frequent site of ocular metastasis is the choroid. The occurrence of choroidal metastases has increased steadily due to the longer survival of metastatic patients and the improvement of diagnostic tools. Fundoscopy, ultrasonography, and fluorescein angiography are now complemented by indocyanine green angiography and optical coherence tomography. Choroidal tumor biopsy may also confirm the metastatic nature of the tumor and help to determine the site of the primary malignancy. There is currently no co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
184
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(191 citation statements)
references
References 243 publications
2
184
0
5
Order By: Relevance
“…In the absence of a reliable history of systemic cancer (e.g., subclinical lung cancer), the conundrum of diagnosis can be a challenge for the ocular oncologist. There are many different modalities useful in the differentiation of metastasis from other choroidal masses [ 62 ]. The reports regarding OCTA findings in choroidal metastasis are scarce and most of them counter-intuitively report signal void and hypovascularity in the regions of CM [ 27 , 62 ].…”
Section: Choroidal Metastasesmentioning
confidence: 99%
“…In the absence of a reliable history of systemic cancer (e.g., subclinical lung cancer), the conundrum of diagnosis can be a challenge for the ocular oncologist. There are many different modalities useful in the differentiation of metastasis from other choroidal masses [ 62 ]. The reports regarding OCTA findings in choroidal metastasis are scarce and most of them counter-intuitively report signal void and hypovascularity in the regions of CM [ 27 , 62 ].…”
Section: Choroidal Metastasesmentioning
confidence: 99%
“…It is often accompanied with multi‐organ metastases, and has a poor prognosis because initially these lesions are generally asymptomatic. The breast is the most common primary site for choroidal metastasis, followed by lungs . The survival of such cases with lung primary is no more than six months…”
Section: Discussionmentioning
confidence: 99%
“…The breast is the most common primary site for choroidal metastasis, followed by lungs. 2 The survival of such cases with lung primary is no more than six months. 3 At 32 years old, this is the second youngest case of choroidal metastases secondary to lung cancer so far reported, the youngest reported being 25 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Lesions that are too thick might not be eligible for vPDT, since the wavelength (689 nm) of the laser used will not penetrate the entire tumor. Moreover, visual acuity seems to improve after vPDT probably due to the decrease of subretinal fluid [39].…”
mentioning
confidence: 94%
“…Intravitreal treatment might be a good therapeutic option for patients with a metastatic disease as it preserves the quality of life without reducing clinical effectiveness. Mathis et al suggested beginning with a single dose followed by a monthly as-needed regimen [39]. It could be proposed for multimetastatic patients under systemic chemotherapy with short life expectancy, as it improves or preserves the vision in most cases without time-consuming treatment.…”
mentioning
confidence: 99%